Chemical calculations and introduction to laboratory work in general and inorganic chemistry : learning texts for foreign students - Kohútová, Mária, 1939-; Valent, Aladár (Vydavateľstvo Univerzity Komenského v Bratislave, 2012)
This text is assigned to foreign students in the first year study at Faculty of Pharmacy, Comenius University, Bratislava in subject General and Inorganic Chemistry. Its content involves topics, chemical problems and calculations presented in seminars, as well as in experimental laboratory works. We would like to stress, that this text does not cover all aspects and does not substitute any text book of inorganic chemistry.